Systematic review of interventions for reducing occupational stress in health care workers - Ruotsalainen, Jani; Serra, Consol; Marine, Albert; Verbeek, Jos (Scandinavian Journal of Work, Environment & Health, 2008)
' ' OBJECTIVES ': 'This study evaluated the effectiveness of interventions in reducing stress at work among health care workers. ' ' METHODS ': 'A systematic search was conducted of the literature on reducing stress or burnout in health care workers. The quality of the studies found was then appraised and the results combined. A meta-analysis was performed when appropriate. ' ' RESULTS ': 'Altogether 14 randomized controlled trials, three cluster-randomized trials, and two crossover trials, comprising 2812 participants, were included. Only two trials were of high quality. The following comparisons were possible: person-directed interventions versus no intervention, person–work interface interventions versus no intervention, and organizational interventions versus no intervention. Person-directed interventions can reduce stress [standardized mean difference (SMD) -0.85, 95% confidence interval (95% CI) -1.21 – -0.49] and burnout, measured as emotional exhaustion [weighted mean difference (WMD) -5.82, 95% CI -11.02 – -0.63) and lack of personal accomplishment (WMD -3.61; 95% CI -4.65 – -2.58). They also reduce anxiety, measured as state anxiety (WMD -9.42, 95% CI -16.92 – -1.93) and trait anxiety (WMD -6.91, 95% CI -12.80 – -1.01). Person–work interface interventions can reduce burnout, measured as depersonalization [mean difference (MD) -1.14, 95% CI -2.18 – -0.10]. Organizational interventions can also reduce stress symptoms (MD -0.34; 95% CI -0.62 – -0.06) and general symptoms (MD -2.90, 95% CI -5.16 – -0.64). No harmful effects were reported. ' ' CONCLUSIONS ': 'Limited evidence is available for a small, but probably relevant reduction in stress levels from person-directed, person–work interface, and organizational interventions among health care workers. This finding should lead to a more-active stress management policy in health care institutions. Before large-scale implementation can be advised, larger and better quality trials are needed.
Keywords: anxiety; burnout; cognitive–behavioral therapy; health care worker; intervention; meta-analysis; nurse; occupational stress; review; systematic review